Rancang Bangun Aplikasi Smart Training Berbasis Android Menggunakan Flutter Dengan Metode RAD - layla frida luthfyana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2021)
This paper discusses the creation of an Android-based smart training system using Flutter to overcome training problems in PB companies that are hampered by the Covid-19 Pandemic. The results of the presentation of the smart training system that were made show that this system can be used to overcome this problem. The smart training system created in this study can provide reports on training data that has been done, this data can be accessed by entering the domain address that has been created and the data will be automatically downloaded in excel. The smart training system prototype can be used to replace old systems that are considered less effective, such as phone calls. To employees who have to take part in training, it is replaced by the Firebase cloud messaging feature which will send notifications to the user application if the user is scheduled to attend training. The smart training system has been tested using usability testing which shows a % satisfaction rate of 80.91% which is categorized as very good.